2009
DOI: 10.1088/0022-3727/42/5/055207
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigations of plasma bullets

Abstract: Recently several investigators reported on various means of generating cold plasma jets at atmospheric pressure. More interestingly, these jets turned out to be not continuous plasmas but trains of small high velocity plasma packets/bullets. However, until now little is known of the nature of these ‘bullets’. Here we present experimental insights into the physical and chemical characteristics of bullets. We show that their time of initiation, their velocity and the distance they travel are directly dependent o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

28
241
2
13

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 375 publications
(284 citation statements)
references
References 5 publications
28
241
2
13
Order By: Relevance
“…This is representative of a faster establishment of the discharge in the DBD due to more efficient excitation/ionization of the gas [16,25]. It means that the propagation velocity of the guided streamers is also amplified, which was confirmed in [16,29,30,44]. Depending on the duty cycle value, ΔtGIWs decreases from ~250 ns at Vp = 6 kV to ~100 ns at Vp = 8 kV, values that are in the range of the ones published in the bibliography [16,25].…”
Section: Effect Of the Voltage Amplitude (Vp) And Duty Cycle (D) On Isupporting
confidence: 51%
See 1 more Smart Citation
“…This is representative of a faster establishment of the discharge in the DBD due to more efficient excitation/ionization of the gas [16,25]. It means that the propagation velocity of the guided streamers is also amplified, which was confirmed in [16,29,30,44]. Depending on the duty cycle value, ΔtGIWs decreases from ~250 ns at Vp = 6 kV to ~100 ns at Vp = 8 kV, values that are in the range of the ones published in the bibliography [16,25].…”
Section: Effect Of the Voltage Amplitude (Vp) And Duty Cycle (D) On Isupporting
confidence: 51%
“…Other studies, referring to similar designs do exist as well [27][28][29][30][31]. Although, the electrodes that are used therein are in the form of very thin rings, which are entirely enclosed in the dielectric material, thus avoiding any contact with the atmospheric air for better insulation.…”
Section: Introductionmentioning
confidence: 99%
“…Recent numerical simulations and experimental studies have made significant advances in the understanding of the cold plasma jets [10][11][12][13][14][15][16] . The detailed studies have revealed that the cold plasma jet produced by nano-second or micro-second pulsed discharges is typically composed of a series of rapidly propagation streamer discharges.…”
Section: Introductionmentioning
confidence: 99%
“…The detailed studies have revealed that the cold plasma jet produced by nano-second or micro-second pulsed discharges is typically composed of a series of rapidly propagation streamer discharges. The streamer with a luminous head propagates at very high speed in order of 10 4 -10 5 m/s over several centimeters 15,17,18 . The experimental images reveal that the luminous zone of the helium plasma jet is a ring-shaped [13], and the peak of luminance is shifted off the jet axis 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Although the discharges in plasma jets typically appear as continuous plasma, high-speed imaging shows that the plasma in fact comprises discrete, fast moving plasma bullets [10][11][12], or ionization waves (IWs). The plasma jet strongly resembles the cathode-directed streamers in some aspects, and some authors speculated that it may be initiated in a way independent of the capillary dielectric barrier discharge [13].…”
Section: Introductionmentioning
confidence: 99%